Development of Environmental Awareness Education Model Guidebook in Sekolah Sungai Winongo - Hiryanto, Hiryanto; Wibawa, Lutfi; Wijayanto, Arif; Tohani, Entoh; Rofiq, Akhmad (Journal of Nonformal Education, 2023)
The “sekolah sungai” is an effort to make the community aware of preserving the environment. It is necessary to have a guide book for the implementation of the  sekolah sungai Winongo  so that it is easily understood by all members of the river school. This study aims to produce a guide book for environmentally conscious education models at the sekolah sungai Winongo. This research is a development research with the ADDIE model, which is carried out until the development stage or model development. Data were collected using interviews, observation and assessment of design and product feasibility. Analysis of the initial condition data was carried out descriptively, the feasibility of the product was carried out by the opinion of the river school material expert, the learning media expert was statistically quantitative using the percentage of success of the model. The results of the study were in the form of a guidebook for the model of environmentally conscious education at the Sekolah Sungai Winongo. The results of expert validation and material validation are in very good criteria and are ready to be tested.